Imagine your life at 25: Gender conformity and later-life outcomes - Sreevidya Ayyar; Uta Bolt; Eric French; Cormac O'Dea (The Institute for Fiscal Studies (IFS), 2024)
Using a digitized sample of thousands of essays written by 11-year-olds in 1969, we construct an index which measures the extent to which girls' imagined futures conform to gender norms in Britain at the time. We link this index to outcomes over the life-cycle. Conditional on a large set of age-11 covariates, a one standard deviation increase in our index is associated with a decrease in lifetime earnings of 3.5%, due to both lower wages and fewer hours worked. Half of this earnings decline is mediated by reduced educational attainment, selection into lower-paid occupations, and earlier family formation of those who conform more strongly to prevalent gender norms. Holding skills constant, girls whose essays conform less to gender norms, live in regions with higher female employment and educational attainment. This highlights that the wider environment in which girls grow up shapes gender conformity.
Keywords: J16; J13; Z13; 330; Gender; Children; Text Analysis